2020
DOI: 10.1002/jia2.25451
|View full text |Cite
|
Sign up to set email alerts
|

Modelling impact and cost‐effectiveness of oral pre‐exposure prophylaxis in 13 low‐resource countries

Abstract: Introduction Oral pre‐exposure prophylaxis (PrEP) provision is a priority intervention for high HIV prevalence settings and populations at substantial risk of HIV acquisition. This mathematical modelling analysis estimated the impact, cost and cost‐effectiveness of scaling up oral PrEP in 13 countries. Methods We projected the impact and cost‐effectiveness of oral PrEP between 2018 and 2030 using a combination of the Incidence Patterns Model and the Goals model. We created four PrEP rollout scenarios involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“… 27 , 28 The inclusion of PrEP services for adolescent girls and young women, primarily in the African region, has resulted in a large increase in young women having received PrEP. This increasing use of PrEP has potential to decrease HIV incidence, particularly in more generalised epidemics, 29 although PrEP continuation has been a challenge. 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 , 28 The inclusion of PrEP services for adolescent girls and young women, primarily in the African region, has resulted in a large increase in young women having received PrEP. This increasing use of PrEP has potential to decrease HIV incidence, particularly in more generalised epidemics, 29 although PrEP continuation has been a challenge. 23 …”
Section: Discussionmentioning
confidence: 99%
“…27,28 The inclusion of PrEP services for adolescent girls and young women, primarily in the African region, has resulted in a large increase in young women having received PrEP. This increasing use of PrEP has potential to decrease HIV incidence, particularly in more generalised epidemics, 29 although PrEP continuation has been a challenge. 23 Although we made every effort to obtain the most upto-date PrEP user data and to ensure that these data had been verified, information was missing for some countries.…”
Section: Table: Oral Prep Users Globally By Subpopulation In 2019mentioning
confidence: 99%
“…PrEP implementation programs have demonstrated the feasibility of delivering PrEP in a variety of settings [5][6][7][8]. If implemented successfully, use of oral PrEP among Ugandan female sex workers (FSW), serodiscordant couples (SDC), and adolescent girls and young women (AGYW), alone, could prevent nearly 9% of anticipated HIV infections from 2018 to 2030 [9]. While the number of countries implementing PrEP has increased in recent years, sub-Saharan Africa accounts for only 44% of global PrEP initiations despite accounting for more than 70% of the global burden of HIV infection [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As the impact of PrEP on the HIV epidemic depends on the network characteristics of not just the PrEP recipients, but also their partners, and their partners' partners, the use of a network-based model allows for realistic estimation of community-level health benefits. Previous mathematical modelling [33] demonstrated that earmarking prevention interventions to key population groups like female sex workers can significantly reduce HIV incidence, but large-scale impact in mature epidemics will require interventions for both key and non-key populations [34]. Indeed, our analyses showed the impact for a given set of resources may still be high when directed to a less connected, but more at-risk, population group, highlighting the importance of providing PrEP to general population groups at elevated risk.…”
Section: Discussionmentioning
confidence: 99%